Author Correction: Transcriptome and functional analysis reveals hybrid vigor for oil biosynthesis in oil palm - Jingjing Jin (Nature Portfolio, 2018)
A correction has been published and is appended to both the HTML and PDF versions of this paper. The error has been fixed in the paper.